2015
DOI: 10.1111/head.12500
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy Outcome Following Prenatal Exposure to Triptan Medications: A Meta‐Analysis

Abstract: The use of triptans during pregnancy does not appear to increase the rates for MCMs or prematurity. The increased rates of spontaneous abortions in the triptan-exposed group and the increased rates of MCM in the migraine no-triptan group require further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 37 publications
1
55
0
9
Order By: Relevance
“…The safety of acute and prophylactic treatment of migraine in pregnancy has previously been assessed . While paracetamol is generally considered safe, NSAID use in the first trimester may increase the risk of miscarriage and birth defects and NSAID use in subsequent trimesters may have adverse effects on neonatal outcomes, including cerebral palsy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of acute and prophylactic treatment of migraine in pregnancy has previously been assessed . While paracetamol is generally considered safe, NSAID use in the first trimester may increase the risk of miscarriage and birth defects and NSAID use in subsequent trimesters may have adverse effects on neonatal outcomes, including cerebral palsy .…”
Section: Discussionmentioning
confidence: 99%
“…While paracetamol is generally considered safe, NSAID use in the first trimester may increase the risk of miscarriage and birth defects and NSAID use in subsequent trimesters may have adverse effects on neonatal outcomes, including cerebral palsy . A meta‐analysis of 6 studies found no increased risk of miscarriage, preterm delivery, and birth defects in triptan‐exposed migraine patients compared with triptan‐unexposed migraine patients, but an increased risk of miscarriage was found when the triptan‐exposed migraine patients were compared with healthy controls without migraine . While effective as migraine prophylaxis, use of beta‐blockers may increase the risk of some neonatal outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…There are virtually no treatments for headache disorders that lack any potential for teratogenicity. Common acute treatments such as NSAIDs are generally avoided during most of pregnancy, ergotamine compounds are contraindicated, and though the emerging evidence suggests safety for occasional use of triptans, regular and repeated use in pregnant women is of uncertain safety. More established preventative therapies including beta‐blockers, tricyclic antidepressants, antiepileptic drugs, and onabotulinumtoxinA all may have the potential for crossing the placenta and teratogenicity of varying degrees .…”
Section: Neuromodulation In Special Populationsmentioning
confidence: 99%
“…12,13 Sumatriptan exposure has not been associated with fetal malformations or adverse outcomes and, if other treatments have failed, it may be used to treat acute migraine attacks. If attacks are frequent, then prophylactic medication should be considered.…”
mentioning
confidence: 99%